Low triglyceride levels are associated with increased risk of immune-related adverse events in patients receiving immune checkpoint inhibitors - Nora Möhn; Emily Narten; Laura Duzzi; Janin Thomas; Lea Grote-Levi; Gernot Beutel; Tabea Fröhlich; Benjamin-Alexander Bollmann; Thomas Wirth; Imke von Wasielewski; Ralf Gutzmer; Florian Heidel; et al. (OncoImmunology)
Immune checkpoint inhibitors (ICI) have revolutionized cancer therapy by enhancing anti-tumor immune responses, yet their use can lead to immune-related adverse events (irAE), including neurological complications. Despite their clinical relevance, predictive biomarkers for irAE remain scarce, and early identification of at-risk patients is a major unmet need. In this prospective study, 200 patients undergoing ICI therapy were enrolled, of whom 59 underwent longitudinal metabolomic profiling at baseline, three months, and six months. Thirty-two patients who developed irAE were compared to 27 age- and sex-matched individuals without irAE. Multivariate analyses, including Principal Component Analysis (PCA) and Partial Least Squares Discriminant Analysis (PLS-DA), revealed distinct metabolomic signatures differentiating the two groups. Notably, baseline levels of triglyceride 20:0_34:1 were significantly lower in irAE(+) patients. In female patients, additional triglyceride species—20:1_34:2, 20:2_34:2, and 20:2_34:3—were also reduced prior to therapy and showed increases within three months of ICI initiation. These findings suggest that specific triglyceride species may serve as early biomarkers for irAE risk, particularly in female patients. The observed dynamic changes point to a potential link between lipid metabolism and immune-related toxicity, supporting the integration of metabolomic profiling into future strategies for risk stratification and personalized monitoring in cancer immunotherapy.